The press and Internet: the shift from printed to online news. The readers of newspapers within Information and Knowledge Society - Ramos Fandiño, Guadalupe Patricia; Larrañaga Rubio, Julio (Revista General de Información y Documentación, 2013)
This paper studies the main effects of Internet on newspapers. The main features concerning the demand of online newspapers in Spain are described. In addition two indicators are created to measure the demographic and economic features of readers of online newspapers
Keywords: Internet; online newspapers; content payment; newspaper demand; online readers; printed newspapers.